Aerobic fitness for young athletes: Combining game-based and high-intensity interval training - Harrison, C. B.; Kinugasa, T.; Gill, N.; Kilding, A. E. (International Journal of Sports Medicine, 2015)
This study compared the effect of game-based training (GT) vs. a mix of game-based training and high-intensity interval training (MT) on physical performance characteristics. 26 young athletes (13.9±0.3 years) were assigned to either GT (n=13) or MT (n=13) for 6 weeks. Game-based training consisted of 2×8-11 min 3 vs. 3 `bucketball` SSGs separated by 3 min of passive rest twice per week, while MT consisted of one SSGs session and one high-intensity session of 15?s runs at 90-95% of the speed reached at the end of the 30-15 intermittent fitness test (VIFT) interspersed with 15?s passive recovery. Peak oxygen uptake (V O2peak), VIFT, jump height, and speed were assessed pre- and post-training. Following training, V O2peak (5.5±3.3%; ES=large) improved after MT, whereas VIFT improved after MT (6.6±3.2%; ES, large) and GT (4.2±5.5%, ES=small). 5-m sprint improved after GT (ES=small), while 20 m sprint and jump height were unchanged. In conclusion, while MT and GT were both effective at increasing performance parameters, greater effects were seen following MT. Therefore, MT should be considered as the preferred training method for improving aerobic power in young athletes.